The Kelas Parenting : Pengelolaan Keuangan Rumah Tangga dan Sosialisasi UU Perlindungan Anak Guna Pemenuhan Hak Anak Usia Dini Di Panti Asuhan Payamuba: Kelas Parenting : Pengelolaan Keuangan Rumah Tangga dan Sosialisasi UU Perlindungan Anak Guna Pemenuhan Hak Anak Usia Dini Di Panti Asuhan Payamuba - Rizki Listyono Putro; Muhammad Azam Muttaqien; Azis Akbar Ramadhan (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2026)
The community service activity entitled "Parenting Class: Household Economic Management and Socialization of the Child Protection Law to Fulfill the Rights of Early Childhood Children at the Payamuba Orphanage" aims to increase the capacity of orphanage managers and foster parents in managing family finances and increasing understanding of children's rights and the provisions of the Child Protection Law to ensure the fulfillment of the rights of early childhood children. The implementation method includes interactive counseling, practical workshops on simple budget management and child needs planning, case study simulations, and socialization of relevant articles of the Child Protection Law accompanied by questions and answers and printed educational materials. The activity was carried out face-to-face at the Payamuba Orphanage, Babadan District, Ponorogo Regency using a participatory approach and direct involvement of caregivers and children (according to age). The results of the community service showed an increase in participants' knowledge about household economic management (the average pre-post score increased by 45%), the existence of a ready-to-use family budget plan in 80% of foster Template Artikel BUDIMAS2families, and a significant increase in understanding of children's rights and mechanisms for reporting violence. Recommendations include continued mentoring and the provision of practical modules for the sustainable fulfillment of early childhood rights.